Comparison Between ARIMA And Fourier ARIMA Model To Forecast The Demand Of Electricity In Sulaimani Governorate - Botan Karim Ahmed; Sham Azad Rahim; Bestan Bahaalddin Maaroof; Hindreen Abdullah Taher (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Electric energy is accounted as one of the major goods in human life, and also have a great role in progressing and developing the several sectors as economics, manufactures and any other sector related to daily use. In this study the monthly demand of electricity in Sulaimani governorate have been used, the main goal of the study is to choose appropriate model to forecast the monthly demand of electric in Sulaimani governorate for 12 months in 2020, the analyzing,results and comparison shows that FSARIMA(0,0,0)x(2,1,0)4 is appropriate model for this mission of forecasting which has minimum AIC among the other candidate models that equal to 0.28